Polymorphs and cocrystals: a comparative analysis - Gonnade, Rajesh G.; Sangtani, Ekta (Journal of the Indian Institute of Science, 2017)
Controlling polymorphism has been the subject of vigorous research in the recent past in the pharmaceutical industry due to the distinct physicochemical properties associated with each solid form. Developing cocrystals/salts of active pharmaceutical ingredients (APIs) has gained tremendous research interest in recent years owing to their potential to improve pharmaceutically relevant properties without affecting therapeutic efficacy. It is observed that compounds that exhibit polymorphism and also contain several H bond donor/acceptor groups have a tendency to form cocrystals and sometime even display cocrystal polymorphism, although this tendency cannot be generalized. The aim of this contribution is to correlate crystal structures of some polymorphic APIs and their respective cocrystals to understand the rationale behind a polymorphic compound generating cocrystals. Here, we make an attempt to compare how the conformation of the molecule observed in its polymorphs support the generation of cocrystals/salts. We understand that it is impossible to cover all the polymorphs and their cocrystals/salts available in the CSD; the comparative study has been carried out with a few case studies, wherein APIs displayed polymorphism (conformation) and also formed cocrystals/salts.